Developing Reflexive Skills in Future Social Educators for Enhancing Their Acmeological Competence - Ilyassova, lira; Samettin , Gunduz; Sholpankulova , Gulnar (Pedagogy and Psychology, 2025)
This paper examines the level of reflexive skills among prospective social educators as a foundation for developing acmeological competence. Acmeological competence is essential in the training of social educators, as it enhances their professional competitiveness and effectiveness. This study aimed to explore the significance of reflective skills in the development of acmeological competence among future social educators, as well as to assess the current level of their reflective skill formation. Methodology and Methods. To achieve this, the authors conducted a theoretical analysis of existing literature and utilized a survey method to gather data from prospective social educators. Results. The findings indicate that while the respondents demonstrate an awareness of their strengths and weaknesses, there remains a need for further development in areas such as critical thinking, value awareness, and other key reflective dimensions. Scientific novelty. The study highlights the necessity of designing and implementing specialized techniques or training programs to foster reflective abilities within the educational process for social educators. To achieve higher levels of professional accomplishment, social educators must be able to adjust their behavior, clearly understand their goals, and evaluate their outcomes. Practical significance. Without well-developed abilities in self-awareness and self understanding, the growth of their professional identity and expertise becomes unattainable.